FLUXO DE CARGA EM REDES DE DISTRIBUIÇÃO OPERANDO EM EMERGÊNCIA. - MARTINS, Caio César Costa (2018)
The load flow in an electrical network consists of determining the state of the network, the distribution of flows and some quantities of interest. In this problem, the system modeling is static, does not depends on time. The network is represented by a set of algebraic equations and inequalities. The emergency operation of a distribution network is characterized by noncompliance of the loads with nominal limits, such as line overload limits or sub / overvoltages limits. These conditions, coupled with the high r / x ratio characteristics of the distribution networks, make it difficult the load flow convergence. In order to deal with emergency scenarios, it will be analyzed and discussed the use of a decoupled three-step strategy that can efficiently solve all of these presented scenarios. Three-step methods are subjected to various tests, such as system overhead, load increase, and load modeling. The presence of distributed generation in the Electric Power Distribution Systems is becoming more frequent, therefore, the proposed method is tested in distribution networks with more than one power supply. The method is validated using standard networks of a real distribution network, with 6, 19 and 45 bars.